Safe, Health Working in Health Care in the Shadow of a Pandemic - Riczu, Zsófia (International Journal of Engineering and Management Sciences, 2021)
Safe work that does not endanger health is a complex category, the provision of which creates an obligation on the part of the state, the employer and the employee. The task of the state is to determine the basic requirements for work that does not endanger health and safe, as well as the related rights and obligations, and to develop a national policy on occupational safety and health. As a result of the coronavirus epidemic in early 2020, we have faced a whole new form of accidents at work and occupational diseases. In my study, I want to examine the course of the investigation of the infection that takes place during the pandemic in healthcare work, and the possibilities of remuneration for the duration of the illness.